Impact of Devolution on Local Governance and Service Delivery in Kenya - Kate, Mercy (International Journal of Humanity and Social Sciences, 2023)
Purpose: The main objective of this study was to explore the impact of devolution on local governance and service delivery in Kenya. Methodology: The study adopted a desktop methodology. Desk research refers to secondary data or that which can be collected without fieldwork. Desk research is basically involved in collecting data from existing resources hence it is often considered a low cost technique as compared to field research, as the main cost is involved in executive's time, telephone charges and directories. Thus, the study relied on already published studies, reports and statistics. This secondary data was easily accessed through the online journals and library. Findings: The findings revealed that there exists a contextual and methodological gap relating to the impact of devolution on local governance and service delivery in Kenya. The empirical review revealed the devolution in Kenya has brought about positive changes in local governance and service delivery. To sustain and enhance these gains, it is imperative to prioritize capacity building, accountability, and collaboration among counties. Devolution remains a powerful tool for fostering development and democratizing governance in Kenya, but ongoing commitment and effort are required to ensure its continued success in improving the lives of Kenyan citizens. Unique Contribution to Theory, Practice and Policy: The Decentralization theory, the Public Choice theory and the Institutional theory may be used to anchor future studies on the impact of devolution on local governance and service delivery in Kenya. There is a need for greater coordination and collaboration among counties. Many challenges, such as infrastructure development and resource allocation, transcend county boundaries. Counties should work together on regional development initiatives to maximize their impact and address common issues effectively. The national government can play a facilitating role in promoting inter-county cooperation through the provision of technical assistance and resources.